Low-latitude variations in the geomagnetic field caused by solar wind disturbances - Belenkaya, E. S.; Parunakian, D. A.; Alekseev, I. I.; Kalegaev, V. V.; Blokhina, M. S.; Grigoryan, M. S. (Geomagnetism and Aeronomy, 2014)
In view of the actual question regarding the effect of a solar-wind pressure jump on disturbances in the Earth’s magnetosphere, events with high velocity and density gradients are of special interest. In this work, we consider the response of the current at the dayside magnetopause to these events and the corresponding strengthening of the geomagnetic field in the low-latitude magnetosphere. A transient process is studied that accompanies reconfiguration of the magnetosphere under the effect of disturbances of solar wind parameters. An analytical equation is received for estimation of an increase in the northern component of low-latitude magnetic field of the magnetosphere in a transient current system (transient ring current) versus initial values of the solar-wind velocity and density and their disturbances.